Análise do desfecho clínico de cura, presença de macrófagos, níveis de citocinas e expressão da anexina-A1 durante a infecção tegumentar dos pacientes com Leishmania braziliensis - Silva, Joselina Maria da (2024)
Cutaneous leishmaniasis (CL) is a disease caused by protozoa of the genus Leishmania, with Leishmania braziliensis being a common causative agent in Brazil. This condition results in ulcerative skin lesions, primarily in exposed areas, leading to scarring, disfigurement, and, in some cases, disability. The immune system, especially macrophages, plays a crucial role in the response to infection. The activation of M1 macrophages, associated with the Th1 response, promotes parasite elimination, while M2 macrophage activation, linked to the Th2 response, may facilitate parasite proliferation and worsen the disease. This study analysed the clinical outcome of CL and patients' immunological profiles, specifically the presence of M1 and M2 macrophages in inflamed sites, local cytokine levels, and the expression of annexin-A1 (ANXA1). The results show that patients with ECR-type lesions within 90 days exhibited a significant increase in M1 macrophages, whereas those who achieved healing within 180 days displayed a higher number of M2 macrophages. In patients with ENR-type lesions, there was no significant difference in the numbers of M1 and M2 macrophages. Additionally, cytokine levels varied according to the lesion type and healing time. Pro-inflammatory cytokines such as IFN-γ and TNF-α were higher in healing ECR lesions within 90 days (P<0.05), while IL-9 and IL-10 were elevated in both ECR and EGR lesions healing after 180 days (P<0.001). TGF-β, IL-21, and IL-23 increased in patients with ECR and EGR lesions who healed after 180 days (P<0.05). The expression of ANXA1, a molecule associated with inflammation resolution, was higher in M2 macrophages in ECR-type skin lesions in patients who healed after 180 days (P<0.05). In conclusion, this study suggests that the infectious microenvironment induced by L. braziliensis affects the differentiation of M1 and M2 macrophages, cytokine levels, and ANXA1 expression specifically, altering patients' healing capacity. Therefore, histopathological and immunological investigations may be used to improve the choice of therapy for CL.